Hubungan Asupan Kafein dengan Tekanan Darah pada Pekerja Bagian Produksi PT Tiga Serangkai Surakarta - Devi, Azzahra Vania Sarah, Elida Soviana, S.Gz., M.Gizi, Siti Zulaekah, A., M.Si (2016)
Background : The negative impact of workers with blood pressure can be seen from their decreasing working performance on the aspect of stamina, working speed and effeciency. This problem can be dangerous aspect in effecting the workers productivity and the company as well. One of the factors causing blood pressure by binding the adenosine receptor that activate the sympathetic nervous system which has impact in increasing total peripheral resistance and the vasocontruction. Objective : To find the relationship between caffeine intake and blood pressure to workers at production division in PT Tiga Serangkai Surakarta. Metods : This study used observational reserch method and cross sectional approach. The object of the study was 38 workers in production division of PT Tiga Serangkai Surakarta and the reserch used consecutive sampling technique. Caffeine intake data was obtained using semi-quantitative FFQ method, obtained from the blood pressure measurement using a sphygmomanometer. Statistical test used is the Spearman Rank test. Results : The percentage of caffeine intake was 44.7%, the percentage of prehypertension systolic blood pressure by 15.8% and the percentage of diastolic pressure prehypertension 44.7%. The relationship test caffeine intake with systolic blood pressure showed the value of p = 0.608 and test relationships caffeine intake with diastolic blood pressure showed the value of p = 0.162. Conclusion: There is no relationship between caffeine intake with blood pressure in production workers PT Tiga Serangkai Surakarta.